2011
DOI: 10.1016/j.ejcts.2011.01.082
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender on mortality in patients after thoracic endovascular aortic repair

Abstract: Gender does not affect mortality in patients after TEVAR irrespective of the underlying indication, atherosclerotic aneurysms, acute type B dissections, penetrating ulcers/intramural hematoma, and traumatic aortic lesions. Classical risk factors such as age and the presence of COPD at the time of TEVAR remain the most important risk factors in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…The median age of our cohort corresponded well to recently published series [10,11]. Interestingly, the number of females in this cohort was lower than in other cohorts of acute type B aortic dissection [12]. The incidence of complicated acute type B aortic dissection was higher than in the recent literature [13].…”
Section: Discussionsupporting
confidence: 86%
“…The median age of our cohort corresponded well to recently published series [10,11]. Interestingly, the number of females in this cohort was lower than in other cohorts of acute type B aortic dissection [12]. The incidence of complicated acute type B aortic dissection was higher than in the recent literature [13].…”
Section: Discussionsupporting
confidence: 86%
“…[1][2][3][4][5][6][7][8][9][10] Women undergoing vascular surgery have been found to have higher mortality rates, more wound complications, greater need for blood transfusion, and increased length of stay. [1][2][3][4][5] In trauma surgery, male sex has been associated with increased mortality, length of stay, and complications. 7 In a broad study of patients undergoing orthopedic surgery, Molina et al 6 found that female sex was an independent risk factor for several complications, including urinary tract infection (UTI), pneumonia, deep surgical site infection (SSI), return to the operating room, and death.…”
Section: Introductionmentioning
confidence: 99%
“…810 Institutional studies assessing sex differences following TEVAR have suggested no difference in mortality, although these were limited by small sample sizes. 11, 12 One recent, large retrospective study of TEVAR using NSQIP data showed female sex to be associated with increased 30-day mortality. 13 However, the association lost statistical significance after adjusting for intraoperative variables, including operative time and use of iliac artery exposure, suggesting the mortality difference may be, in part, explained by varying aortoiliac and femoral arterial disease burden between sexes.…”
Section: Introductionmentioning
confidence: 99%